Investigation into the origins of an ancient BRCA1 founder mutation identified among Chinese families in Singapore. Issue 3 (21st August 2020) - Shaw, Tarryn; Chan, Sock Hoai; Teo, Jing Xian; Chong, Siao Ting; Li, Shao‐Tzu; Courtney, Eliza; Ishak, Diana; Sankar, Haresh; Ang, Zoe Li Ting; Chiang, Jianbang; Loh, Marie; Zhou, Li; et al.
Abstract: Identification of ancestry‐specific pathogenic variants is imperative for diagnostic, treatment, management and prevention strategies, and to understand penetrance/modifiers on risk. Our study aimed to determine the clinical significance of a recurrent BRCA1 c.442‐22_442‐13del variant of unknown significance identified among 13 carriers from six Chinese families, all with a significant history of breast and/or ovarian cancer. We further aimed to establish whether this was due to a founder effect and explore its origins. Haplotype analysis, using nine microsatellite markers encompassing 2.5 megabase pairs around the BRCA1 locus, identified a common haploblock specific to the variant carriers, confirming a founder effect. Variant age was estimated to date back 77.9 generations to 69 bc using the Gamma approach . On principal component analysis using single nucleotide polymorphisms merged with 1000 Genomes dataset, variant carriers were observed to overlap predominantly with the southern Han Chinese population. To determine pathogenicity of the variant, we assessed the functional effect on RAD51 foci formation as well as replication fork stability upon induction of DNA damage and observed an impaired DNA repair response associated with the variant. In summary, we identified an ancient Chinese founder mutation dating back 77.9 generations, possibly common among individuals of southern Han Chinese descent. Using evidence from phenotypic/family history studies, segregation analysis and functional characterization, the BRCA1 variant was reclassified from uncertain significance to pathogenic. Abstract : What's new? Extensive databases of BRCA1/2 variants have helped researchers develop diagnostic and treatment strategies for breast cancer. However, most of this information has been obtained from populations of European descent. In the present study, the authors were able to identify an ancient founder mutation in BRCA1 that is pathogenic and may be common among individuals of Han Chinese descent. In addition to its importance for appropriate patient care, this approach to studying ancestry‐specific variants may also aid in developing techniques to detect pathogenic mutations that might otherwise be missed.